Pentingnya Stepping the 5 Stairs â€œAâ€ Teknik Untuk Anak-Anak Pesisir yang Belajar Grammar - Satria Agust; Gatot Subroto; Muhammad Candra (Fakultas Keguruan dan Ilmu Pendidikan Universitas Maritim Raja Ali Haji, 2019)
The English learning experience especially Grammar should be done in a fun way and make the language learners master the concept well. The importance of mastering Grammar well facilitates language learners to construct English sentences from various tenses. Coastal language learners have not been given good grammar understanding and do not have enough time to learn grammar in schools. To master Grammar, Stepping the 5 Stairs